In vitro transcription of two Epstein-Barr virus specified small RNA molecules. - Jat, P (1982)
Cloned DNA from the EcoRI J fragment of EBV has been used as template for in vitro transcription experiments using cell-free extracts prepared from HeLa or KB cells. Two EBV specific RNAs each about 175 bases in length were synthesised and nuclease 51 mapping experiments determined that these in vitro products corresponded precisely to the in vivo species obtained from Raji cells. These two RNA molecules are transcribed by RNA polymerase III and in common with other pol III-synthesised RNAs the coding sequences contain intragenic control regions. The relative abundance of the two RNAs synthesised in vitro differs from that observed in vivo.